Human adipose tissue gene expression of solute carrier family 19 member 3 (SLC19A3); relation to obesity and weight‐loss. (30th June 2021) - Pereira, Maria J.; Andersson‐Assarsson, Johanna C.; Jacobson, Peter; Kamble, Prasad; Taube, Magdalena; Sjöholm, Kajsa; Carlsson, Lena M. S.; Svensson, Per‐Arne
Abstract: Objective: Adipose tissue is a specialized endocrine organ that is involved in modulating whole‐body energy homeostasis and expresses a specific subset of genes, which may play a role in adipose tissue metabolism. The aim of this study was to search for novel adipose tissue‐specific genes using a tissue panel of RNAseq expression profiles. Methods: RNAseq expression profiles from 53 human tissues were downloaded from the GTex database. SLC19A3 expression was analyzed by microarray or real‐time PCR in two sets of paired subcutaneous and omental adipose tissue samples, in two studies with adipose tissue from persons with high or low body mass index (BMI), in adipose tissue from patients who underwent weight loss with a very‐low caloric diet and during preadipocyte‐adipocyte differentiation. Results: The RNAseq‐based tissue distribution expression screen identified SLC19A3 (encoding the thiamine transporter 2) as adipose tissue‐specific. SLC19A3 expression was higher in subcutaneous compared with omental adipose tissue in both sample sets ( p  = 0.043 and p  < 0.001). Preadipocyte differentiation towards adipocytes resulted in increased SLC19A3 gene expression ( p  = 0.018 or less at all‐time points). Subcutaneous adipose tissue expression of SLC19A3 was lower in persons with high BMI in both cohorts ( p  = 0.008, and p  < 0.001) and increased during a weight‐loss intervention ( p  = 0.006). Conclusion: The specific adipose tissue expression pattern of SLC19A3, together with its regulation in obesity and during weight loss, indicate that it plays a key role in adipocyte metabolism.